East Lampung Cassava Farmers’ Decision to Adopt Double Row Cultivation Technique - Ibnu, Muhammad (Universitas Djuanda, 2023)
Even though it has the potential to increase cassava production, the level of application or adoption of the double row cultivation technique by cassava farmers seems to be unsatisfactory. This study aims to evaluate the variables that influence cassava farmers' decisions to adopt double row cultivation techniques. This research was conducted in Muara Jaya Village and Sukadana Ilir Village, Sukadana District, East Lampung Regency from September to November 2022. The cassava farmers surveyed (systematically randomized) totaled 200 people, and the quantitative analysis used was heckprobit regression (which able to minimize selection bias and probability bias). The results showed that farmers' decisions to adopt double row cultivation techniques were directly and significantly influenced by barriers to selling to factories and non-factories, the number of family dependents, the farmer's side job, the type of commodity planted, input constraints, the activeness of farmer groups, and perceptions farmers to technology. Thus, it was concluded that the decision-making process of farmers adopting cultivation technology is quite complex, and is a combination of on-farm and off-farm considerations.